A Technique For Visualisation Of Latent Fingerprints Turmeric ( Curcuma Aromatica) Powder On Walls And Floor. - Aleena Alex, Dr. Abirami Arthanari, S Rajeshkumar (Drugs and Cell Therapies in Hematology, 2021)
Introduction-The Forensic scientists have exposed a number of ways for recovering usable fingerprints that divulge the identity of the person involved or linked to the felony. There are numerous incremental progressions made over decades by introducing different powder formulations for the development of latent fingerprints which can overcome the use of chemicals which are toxic and pose potential health jeopardies. Aim- The aim of the study is to find a new technique for visualisation and analysis of latent fingerprints using curcuma aromatica on floors and walls. Materials and methods: The various methods have been found for the development of latent fingerprints on different surfaces. The paper presents a new powdering method which is simple, non-toxic for the development of latent fingerprints that can be employed on different substrates. The application of the powder on the print is by brushing which is a simple and an easy technique but it also has disadvantages that if the brush on coming in contact with the surface having the print destroys the print and hence the ridge characteristics will get destroyed. Results- These results have suggested that the turmeric powder can be successfully employed as a powder on the majority of surfaces Conclusion- The concluded that turmeric powder which is easily available, non-toxic and simple can be used successfully on various surfaces to develop the prints in crime investigations.